Asymmetric mitoses revealed by AgNORs in developing rat blood cells - Likovský, Z; Smetana, K (Life sciences, 1995)
Immature cells of erythroid as well as granulocytic series were studied in rat hemopoietic bone marrows to provide a basic information on the asymmetric distribution of AgNORs in anaphases and telophases of these cells. The results clearly demonstrated that such asymmetric mitotic divisions with respect to the distribution of AgNORs to future daughter nuclei represent a regular phenomenon in the course of erythroid as well as granulocytic maturation and thus are not limited to neoplastic cells in which this phenomenon was described previously.
Keywords: Animals; telofáze; Rats, Wistar; anafáze; Hematopoietic Stem Cells; Silver Staining; erytrocyty; organizátor jadérka; Bone Marrow; Mitosis; mitóza; Telophase; kostní dřeň; Male; Erythrocytes; granulocyty; Nucleolus Organizer Region; hematopoetické kmenové buňky; krysa rodu Rattus; barvení stříbrem; Granulocytes; Anaphase; zvířata; mužské pohlaví; Rats; potkani Wistar